Local Heating Test for Detection of Microcirculation Abnormalities in Patients with Diabetes-Related Foot Complications. (April 2017) - Parshakov, Aleksey; Zubareva, Nadezhda; Podtaev, Sergey; Frick, Peter
ABSTRACT: OBJECTIVE: In this study, authors used a wavelet analysis of skin temperature (WAST) to assess the mechanisms of microvascular tone regulation during the local heating test in patients with diabetic foot syndrome (DFS). PARTICIPANTS: The participants included control subjects and 36 hospitalized patients with DFS between 52 and 79 years old (68 ± 8 years old). They were distributed among 5 groups: 15 control subjects, 8 patients with DFS who did not develop ulcerative or necrotic disorders, 10 patients who developed the neuroischemic form of DFS complicated by foot ulceration, 12 patients with DFS complicated by toe necrosis, and 6 patients with DFS and foot gangrene. OUTCOME MEASURES: A comparison among the groups was made using a nonparametric Mann-Whitney U test. Spearman correlation coefficients were used to assess the relationship between WAST results, aortoarteriography, and ultrasonic dopplerography data. MAIN RESULTS: In control subjects, a local increase in temperature (up to 42° C) causes a more than 3-fold increase in the amplitude of foot skin temperature oscillations. In patients with DFS, the response to the local heating test was much weaker. High correlations of WAST results to arterial patency of the lower extremities and the state of the vascular walls were established. CONCLUSIONS: The WAST technique may have considerable value in evaluating the progression of DFS and the effectiveness of therapeutic interventions. The low cost of an individual test makes the WAST technique suitable for routine use in most healthcare facilities.